Pulsed Cathodoluminescence of LiF Crystals Doped with W and Ti; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Korepanov V. I. Vladimir Ivanovich; Petikar P. V. Pavel Viktorovich; Ge Guanghui (Guang Hui Ge); Li Y. Y. Yan Yi (Materials and Technologies in Optoelectronics Production, 2016)
Title screen